Conceptual Level on Electricity in Logical-Mathematical and Naturalist Intelligence of Elementary School Students - Hamid, Rimba; B., Amiruddin (Mimbar Sekolah Dasar, 2023)
Abstract. For a teacher who teaches science concepts to a group of students, they ought to investigate the level of understanding from various background, including one of the differences in the dominant multiple intelligences (MI) possessed by students. This level of understanding can be identified from the ability of students to understand concepts in a series of learning phases through tests of understanding the initial concepts and final concepts of a topic of teaching material. This study aims to map the level of conceptual change in electricity based on two types of elementary school students' MI, namely logical-mathematical intelligence and naturalist intelligence through a problem-based learning model with a scientific approach and experimental methods. The research findings show that 1) the profile of students' multiple intelligence levels in the logical-mathematical type of intelligence has a relatively similar trend pattern with naturalist intelligence in the subjects studied and in the learning process about electricity; 2) students are distributed at the level of understanding based on their conceptual change from initial understanding to final understanding in almost all categories, with the largest percentage (47.83%) of students being at the level of revising with 4 different variants, and 4.35% of students being at the level of complete their knowledge; and 3) students' understanding of the concept of electricity is randomly distributed at all conceptual levels, both on the type of logical-mathematical multiple intelligence and on the type of naturalist intelligence.